My mini mat / Raihana Alia, Alya Zahra and Alyssa Nur Ain - -, Raihana Alia; -, Alya Zahra; -, Alyssa Nur Ain (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
This paper examines product design research in the broad field of business studies. It organizes established and emergent concepts and ways of approaching three key areas that correspond to various stages of the development innovation process. Coop.inc manufactures a variety of handmade goods that maintains a good quality for our customer’s daily basic needs. The MMM (My Mini Mat) is a multifunctional tote bag that can be turned into a prayer mat for Muslims of all ages.